MONITORING THE TEMPERATURE OF REFRIGERATION COUNTERS AND BEEF SOLD IN BUTCHER SHOPS IN THE CITY OF CAMETÁ IN THE STATE OF PARÁ, BRAZIL. - ALMEIDA, M. C. S.; BRITO, P. A.; DANTAS, V. V.; PRAZERES, A. R.; SILVA, E. V. C.; SILVA, J. B. (Ars Veterinaria, 2022)
Meat is a very perishable product with a short shelf life, so the use of low temperatures is used to reduce the speed of chemical reactions, inhibit the growth of microorganisms, thus increasing the shelf life of this food. The objective of this work was to evaluate the temperature of fresh beef in refrigeration counters, and to monitor the temperature of this equipment in the butcher shop in the city of Cametá, Pará, Brazil, comparing it with the current legislation. In total, fifteen butcher shops were selected for this study, a skewer thermometer was used to measure the temperature of the meat, and a digital infrared thermometer was used for the counters. A statistical analysis was performed using Student's T test, using the average temperatures of the meats and the counters. It was found that among the temperatures, 23,33% of the meat samples (7/30) had their averages above the reference average (7°C), as well as the temperatures of the counters with 86,66% of the equipment (13/15), had an average temperature above the legal limit, which is 7°C. The study showed that the temperature of the counters and beef in the butchers were out of the quality standard, therefore a risk to consumer health, requiring stricter inspection and training of employees by public agencies.